1991
DOI: 10.1061/(asce)0733-9429(1991)117:10(1389)
|View full text |Cite
|
Sign up to set email alerts
|

Solution of Three‐Constraint Entropy‐Based Velocity Distribution

Abstract: A two-dimensional velocity profile based upon the principle of maximum entropy (POME) for wide open channel flows is presented. The derivation is based on the conservation of mass and momentum. The resulting profile involves three parameters that are determined from observations of mean velocity and the velocity at the water surface. The velocity profile is verified using field data in a river with a live bed. A comparison with three existing methods shows that the profile presented is the most accurate of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(16 citation statements)
references
References 4 publications
0
16
0
Order By: Relevance
“…The maximum entropy formulation was developed by [40,41]. The principle of maximum entropy (POME) proposes that if inferences are to be made based on incomplete information, they should be drawn from the probability distribution that has maximum entropy permitted by the information that is already available [42]. Based on this concept, Al-Hamdan and Cruise [22] developed an entropy-based model for simulating soil moisture profiles corresponding to all phases of the physical process.…”
Section: Entropy Applied To Soil Moisture Statesmentioning
confidence: 99%
See 1 more Smart Citation
“…The maximum entropy formulation was developed by [40,41]. The principle of maximum entropy (POME) proposes that if inferences are to be made based on incomplete information, they should be drawn from the probability distribution that has maximum entropy permitted by the information that is already available [42]. Based on this concept, Al-Hamdan and Cruise [22] developed an entropy-based model for simulating soil moisture profiles corresponding to all phases of the physical process.…”
Section: Entropy Applied To Soil Moisture Statesmentioning
confidence: 99%
“…Relationships between the Lagrange multipliers and the constraints and boundary conditions have also been developed, as in the first case, with the resulting system of nonlinear equations solved for the multipliers by a technique given by Barbe et al [42]. Finally, Al-Hamdan and Cruise [22] demonstrated that the third case (dynamic) can be handled by a combination of the wet and dry profiles.…”
Section: Development Of Soil Moisture Profiles From Pomementioning
confidence: 99%
“…However, estimation of two-dimensional velocity distribution is not always simple and may require as many as six parameters (Chiu & Chiou 1986). The probability density function of the velocity was then obtained by applying the maximum entropy principle (Barbé et al 1991;Chiu 1987Chiu ,1988Chiu ,1989. Using this probabilistic formulation, the mean velocity, u^, can be expressed as a linear function of the maximum velocity, u,"ax, through a dimensionless entropy parameter M (Chiu 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Relationships between the Lagrange multipliers and the constraints and boundary conditions have also been developed, as in the first case, with the resulting system of nonlinear equations solved for the multipliers by a technique given by Barbe et al [66].…”
Section: Development Of Soil Moisture Profiles From Alexi Awmentioning
confidence: 99%